In vitro antimicrobial evaluation of pyrazolone derivatives - Ahar, Leile Rahimi; Sadr, Moayad Hossaini; Zare, Karim; Tabatabaei, Samad Motameni (Bangladesh Journal of Pharmacology, 2015)
In this investigation, unsubstituted pyrazolin-3(5)-ones (MePzO= 3-methyl-5-pyrazolone, PrPzO= 3-propyl-5-pyrazolone and PhPzO= 3-phenyl-5-pyrazolone) have been synthesized. The synthesized compounds were also screened for their antibacterial activity against some Gram-positive and Gram-negative bacteria using agar well diffusion method. The compounds with different concentrations were prepared and the activity was determined by measuring the diameter of the inhibition zone (in mm). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the compounds were determined against six bacteria. The antibacterial activities were influenced functional groups (methyl, propyl and phenyl). PhPzO exhibited the strongest activity (MIC, 0.625 mg/mL; MBC, 2.5 mg/mL) against Bacillus subtilis.